Perencanaan Embankment / Timbunan Diatas Tanah Lunak Disungai Harus Kalimantan Selatan - Noor Jannah; Agus Sulaiman (Pusat Riset dan Inovasi Nasional, 2023)
The planning of embankment on soft soil at the Harus River, South Kalimantan, is an area owned by a mining company. This area is planned to be developed into a transportation route, which will later function as an alternative transportation route to accelerate the transportation of the company's mining products. The embankment planning is located directly on soft soil. According to Geotechnical guidelines 1, Pedoman Kimpraswil: Pt T-8-2002-B, soft soil refers to soil that, if not properly identified and investigated, may cause instability and long-term settlement problems that cannot be tolerated because it has low shear strength and high compressibility. Therefore, handling of settlement in soft soil is essential. One alternative for preventing failure in embankment soil is reinforcement. However, in this study, only the height of the embankment is planned without reinforcement. The aim of this study is to determine the safety factor of the embankment on the soil. The analysis of the safety factor is conducted by applying the finite element method with the help of PLAXIS 8.2 software. The data used in this study were obtained from literature and laboratory testing results from SI-ADORADO-GOLDER. Based on the stability calculation of the embankment on soft soil with a height of 1.5 meters per stage and a slope of 1:5, the results obtained from the analysis using the finite element method with PLAXIS 8.2 indicate that the embankment meets the safety factor criterion of 1.4. The slope of the embankment obtained from the PLAXIS 8.2 program is 1.441.